2014
DOI: 10.1016/j.sjbs.2014.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Implication of SH2B1 gene polymorphism studies in gestational diabetes mellitus in Saudi pregnant women

Abstract: Genome-wide association studies have identified loci that are firmly associated with obesity. The Src-homology-2 B adaptor protein 1 (SH2B1) loci is abundantly expressed in the brain, liver, heart, muscle, and fat tissues. Gestational diabetes mellitus (GDM) is a growing health concern that usually appears during the latter half of pregnancy, and it is characterized by carbohydrate intolerance of variable severity. The SH2B1 gene polymorphism has been linked with an increased risk of weight gain in several but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 26 publications
1
8
0
Order By: Relevance
“…In our study, multiple linear regression analysis suggested that OGTT2h, PROM and self‐monitoring of blood glucose (SLMG) times were risk factors for gestational age at delivery. This result was consistent with the findings of Alhakeem . Yao‐Jun et al .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In our study, multiple linear regression analysis suggested that OGTT2h, PROM and self‐monitoring of blood glucose (SLMG) times were risk factors for gestational age at delivery. This result was consistent with the findings of Alhakeem . Yao‐Jun et al .…”
Section: Discussionsupporting
confidence: 93%
“…This result was consistent with the findings of Alhakeem. 11 Yao-Jun et al 12 also showed that premature rupture was the main risk factor for premature delivery. In addition, obstetricians should pay attention to the OGTT2h blood sugar level to increase the gestational age at delivery.…”
Section: Factors Contributing To Gestational Age At Deliverymentioning
confidence: 98%
“…This gene family contains three members of adaptor proteins (SH2B1, 2 and 3), being highly expressed in the liver [22]. Its potential mechanism may be as an adaptor protein, wherein SH2B1 is implicated in several transduction processes such as enhancing JACK2 or the PI3-kinase pathway [23,24]. A genetic disruption of this gene has been associated with severe leptin resistance, energy imbalance, obesity and type 2 diabetes in humans, which are common comorbidities related to NAFLD [24].…”
Section: Introductionmentioning
confidence: 99%
“…Its potential mechanism may be as an adaptor protein, wherein SH2B1 is implicated in several transduction processes such as enhancing JACK2 or the PI3-kinase pathway [23,24]. A genetic disruption of this gene has been associated with severe leptin resistance, energy imbalance, obesity and type 2 diabetes in humans, which are common comorbidities related to NAFLD [24]. In addition, it has been recently published that SH2B1 can regulate the migration, proliferation and differentiation of cells, which could influence the development of some cancers [23].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation